Comparison of the Finnish translations of C.S. Lewis’s The Screwtape Letters - Markkula, Mikael (My University, 2023)
In this thesis the two Finnish translations of C.S. Lewis’s The Screwtape Letters are compared and reasons for the retranslation are suggested. The translations of the whole text are compared, and the “erroneous” words and passages found are classified into two groups according to Pym’s “Binary error vs. non-binary error” -classification. Within these groups the “incorrect” translations are sorted into the following sub-groups: 1) Binary error with incorrect meaning in the translation 2) Binary error with an unidiomatic translation 3) Binary error with an incorrect translation of an idiomatic expression 4) Non-binary error with a slightly unidiomatic translation 5) Non-binary error with a slightly inaccurate translation and 6) Non-binary error with interference in translation. The numbers of different errors are compared. The style and structure of the translations are compared. The introduced theoretical background include the following items: concepts of domestication and foreignization; retranslation hypothesis; effects of earlier translations on retranslation; differences between retranslation and revision; different approaches to literary translation; politics, authority and institutional aspects related to (re)translation; influence of norms and ideologies on (re)translations; aging of translations; translation evaluation and error classification; and language transfer in translation. In Tuulio’s translation 107 binary errors and 54 non-binary errors were found while in Junttila’s translation only three binary errors and two non-binary errors were spotted. The number of errors in Tuulio’s translation seem to be the only reason and motive for the retranslation. Other possible reasons such as changes in the ideological contexts or social norms or in the relationship between British and Finnish cultures do not apply here.
Keywords: retranslation hypothesis, domestication, foreignization, literary translation, translation error classification, interference